The investigation of soil bearing capacity of soft clay soil - Choong Wei Kang (School of Environmental Engineering, University Malaysia Perlis, 2013)
A study was conducted that aimed to improve the general understanding of the bearing capacity of the soft clay soil commonly found in the area near the beach.